14, 16, 34, 36, 54, 56, 74, 76-Octanitro-2, 4, 6, 8-tetraoxa-1, 3, 5, 7(1, 3)-tetrabenzenacyclooctaphane and its derivatives: thermally stable explosives with outstanding properties. (6th June 2017) - Zhang, XingCheng; Xiong, HuaLin; Yang, HongWei; Cheng, Guangbin
Abstract : Herein, the novel, thermally stable explosive 1 4, 1 6, 3 4, 3 6, 5 4, 5 6, 7 4, 7 6 -octanitro-2, 4, 6, 8-tetraoxa-1, 3, 5, 7(1, 3)-tetrabenzenacyclooctaphane (4a ) and its derivatives are reported. Abstract : Herein, the novel, thermally stable explosive 1 4, 1 6, 3 4, 3 6, 5 4, 5 6, 7 4, 7 6 -octanitro-2, 4, 6, 8-tetraoxa-1, 3, 5, 7(1, 3)-tetrabenzenacyclooctaphane (4a ) and its derivatives are reported. These compounds can be prepared via a facile synthetic procedure and show outstanding properties (detonation velocity, detonation pressure, sensitivity towards mechanical stimuli, and temperature of decomposition). Moreover, 4a and its derivatives were isolated and characterized via mass spectrometry and multinuclear ( 1 H, 13 C) NMR spectroscopy. The structures of4a and4b in the crystalline state were determined via low-temperature single-crystal X-ray diffraction. From the calculated standard molar enthalpies of formation (CBS-4M) and densities, the Chapman–Jouguet detonation properties were predicted using the EXPLO5 V6.01 thermochemical computer code. The sensitivities of4a and its derivatives towards impact, friction, and electrostatic discharge were determined.